Local Projections - Jordà, Òscar,Taylor, Alan M. (National Bureau of Economic Research, 2024)
A central question in applied research is to estimate the effect of an exogenous intervention or shock on an outcome. The intervention can affect the outcome and controls on impact and over time. Moreover, there can be subsequent feedback between outcomes, controls and the intervention. Many of these interactions can be untangled using local projections. This method's simplicity makes it a convenient and versatile tool in the empiricist's kit, one that is generalizable to complex settings. This article reviews the state-of-the art for the practitioner, discusses best practices and possible extensions of local projections methods, along with their limitations
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Konjunktur; Finanzpolitik; Multiplikator; Schock; Schätzung; Wirkungsanalyse; Theorie; Econometrics; Semiparametric and Nonparametric Methods: General; Time-Series Models; Dynamic Quantile Regressions; Dynamic Treatment Effect Models; Diffusion Processes; Instrumental Variables (IV) Estimation; Time-Series Models; Dynamic Quantile Regressions; Dynamic Treatment Effect Models; Diffusion Processes; State Space Models; Quantitative Policy Modeling